Relation between cigarette smoking and use of hormonal replacement therapy for menopausal symptoms. Issue 1 (March 1987) - Greenberg, G; Thompson, S G; Meade, T W
Abstract : The aim of this study was to characterise new users of hormonal replacement therapy (HRT) for the relief of menopausal symptoms and to compare these women with never-users of HRT; 402 new users and 804 never-users were studied. Hot flushes were the most common symptom in both users and non-users and were the most frequent reason for prescribing HRT. The prevalence of menopausal symptoms in non-users of HRT was high although substantially lower than that in users. HRT users were more likely to be current cigarette smokers than were never-users. There was also, within smokers, a significant relation between the number of cigarettes smoked and the likelihood of using HRT. This relation between HRT use and smoking could result from an anti-oestrogen effect of smoking, intensifying menopausal symptoms. Of potential clinical relevance is the suggestion that a proportion of women using HRT may be doing so in order to alleviate smoking-induced symptoms. Users of HRT were also more likely to have used oral contraceptives than were never-users; this relation was probably behavioural.